The Meaning of hatha in Early Hathayoga - Birch, J (2011)
This essay was prompted by the question of how Hathayoga, literally 'the Yoga of force', acquired its name. Many Indian and Western scholars have understood the 'force' of Haṭhayoga to refer to the effort required to practice it. Inherent in this understanding is the assumption that Haṭhayoga techniques such as praṇayama (breath control) are strenuous and may even cause pain. Others eschew the notion of force altogether and favor the so-called 'esoteric' definition of Haṭhayoga (i.e, the union of the sun (ha) and moon (ṭha) in the body). This essay examines these interpretations in light of definitions of haṭhayoga and the adverbial uses of haṭha (i.e, haṭhat, haṭhena) in Sanskrit Yoga texts that predate the fifteenth-century Hathapradipika.